Iron deficiency: prevalence, mortality risk, and dietary relationships in general and heart failure populations - Sun, Hui; Wang, Qinhong; Han, Wenqiang; Chen, Changli; Wang, Tianyu; Zhong, Jingquan (Frontiers in Cardiovascular Medicine, 2024)
Background: Iron deficiency (ID) is the most common nutritional deficiency, with little research on its prevalence and long-term outcomes in the general population and those with heart failure (HF). Both the relationships between dietary iron and ID, as well as dietary folate and ID, are understudied. Methods: We used data from the National Health and Nutrition Examination Survey from 1999-2002 to investigate the prevalence, prognosis, and relationship between dietary and ID defined by different criteria in the general population (n=6660) and those with HF (n=182). Results: There was no significant difference in the prevalence of ID between HF patients and the general population after propensity score matching. Transferrin saturation (TSAT) <20% was associated with higher 5-year all-cause mortality (HR: 3.49, CI: 1.40-8.72, P=0.007), while ferritin <30 ng/mL was associated with higher 10-year (HR: 2.70, CI: 1.10-6.67, P=0.031) and 15-year all-cause mortality (HR: 2.64, CI: 1.40-5.00, P=0.003) in HF patients. Higher dietary total folate but dietary iron reduced the risk of ID (defined as ferritin <100 ng/mL) in HF patients (OR: 0.80; 95%CI: 0.65-1.00; P=0.047). Conclusions: The prevalence of ID was identical in HF and non-HF individuals. Ferritin <30 ng/mL was associated with long-term outcomes whereas TSAT <20% was associated with short-term prognosis in both the general population and HF patients. A diet rich in folate might have the potential for prevention and treatment of ID in HF patients.